2003
DOI: 10.1007/s00787-003-0322-6
|View full text |Cite
|
Sign up to set email alerts
|

Help seeking for emotional and behavioural problems in children and adolescents

Abstract: s Abstract In order to understand the discrepancy between rates of child and adolescent psychopathology and rates of mental health service use, variables influencing the help-seeking process need to be investigated. The present article aims to extend and refine previous findings by reviewing 47 recent empirical studies on parental and adolescent problem recognition and help seeking, and problem recognition by the general practitioner (GP). Several variables (child age, the presence of medical and school-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
215
4
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(241 citation statements)
references
References 47 publications
(94 reference statements)
16
215
4
6
Order By: Relevance
“…This association has already been described, although there is no conclusive evidence. 13,18 While many studies reported that females were more likely to seek help than males, 13,18,31,32 no significant sex association was found in the present study. Saunders et al found, in line with the present results, that females were more likely to identify a need for help but that there was no sex difference in obtaining help.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 79%
See 3 more Smart Citations
“…This association has already been described, although there is no conclusive evidence. 13,18 While many studies reported that females were more likely to seek help than males, 13,18,31,32 no significant sex association was found in the present study. Saunders et al found, in line with the present results, that females were more likely to identify a need for help but that there was no sex difference in obtaining help.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 79%
“…These two signs of seriousness increase the likelihood of consulting, either spontaneously or encouraged by family or friends. 9,26 Although studies reported a similar influence of other concomitant psychological problems, such as behaviour disorders (antisocial, aggressive), substance abuse, or problems following sexual or physical abuse, 9,13,18 no significant associations were found in the present study.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 77%
See 2 more Smart Citations
“…Family structure (1 or two parent) (e.g. Zwaanswijk et al, 2003a) and living situation (homeless, in home or out home placement) (Buckner & Bassuk, 1997;McMillen et al, 2005;Sourander et al, 2004) have also been found to be important factors in MHC use. Since URM often live in residential settings in host countries where they do not receive 24 h supervision or only very limited supervision, the discrepancy between the need for MHC as felt by URM themselves and the need as perceived by significant adults could be even greater.…”
mentioning
confidence: 99%